2005
DOI: 10.1359/jbmr.041132
|View full text |Cite
|
Sign up to set email alerts
|

Overweight Postmenopausal Women Lose Bone With Moderate Weight Reduction and 1 g/day Calcium Intake

Abstract: Overweight postmenopausal women may be more susceptible to bone loss with weight reduction than previously studied obese women. The influence of energy restriction and Ca intake on BMD was assessed in 66 individuals. Weight reduction resulted in bone loss at several sites in women consuming 1 g Ca/day and was mitigated with higher calcium intake at 1.7 g/day.Introduction: Bone loss is associated with weight loss in obese postmenopausal women and can be prevented with calcium (Ca) supplementation. However, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
131
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 59 publications
19
131
3
4
Order By: Relevance
“…In addition, we examined whether dietary Ca intake during weight loss was associated with bone turnover and BPb levels. Understanding how weight reduction affects Pb levels is important in light of the high prevalence of dieting and findings that caloric restriction increases bone turnover in susceptible populations (i.e., postmenopausal women or after surgical weight loss; Ricci et al, 2001;Riedt et al, 2005Riedt et al, , 2006. We found that after severe, but not moderate weight loss, BPb levels increase compared to baseline, but are still o13 mg/dl.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, we examined whether dietary Ca intake during weight loss was associated with bone turnover and BPb levels. Understanding how weight reduction affects Pb levels is important in light of the high prevalence of dieting and findings that caloric restriction increases bone turnover in susceptible populations (i.e., postmenopausal women or after surgical weight loss; Ricci et al, 2001;Riedt et al, 2005Riedt et al, , 2006. We found that after severe, but not moderate weight loss, BPb levels increase compared to baseline, but are still o13 mg/dl.…”
Section: Discussionmentioning
confidence: 77%
“…Weight-stable (no change in body weight in past 3 months) women who had been recruited for weight loss and weight maintenance studies within our laboratory from 2002 to 2005 (Riedt et al, 2005(Riedt et al, , 2006(Riedt et al, , 2007. Over a period of 6 months, overweight and moderately obese participants were counseled by a registered dietitian to either maintain their weight (WM group) or to lose a moderate amount of weight (M-WL) using moderate energy restriction of 1200 to 1500 kcal/day and behavior modification.…”
Section: Subjects and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of weight loss on bone mineral remains controversial. Although weight loss in postmenopausal women apparently results in loss of bone mass (Avenell et al, 1994;Ricci et al, 1998Ricci et al, , 2001Riedt et al, 2005;, findings in premenopausal women (Salamone et al, 1999;Fogelholm et al, 2001;Shapses et al, 2001;Park et al, 2007;Riedt et al, 2007) and in middle-aged men (Pritchard et al, 1996; are inconsistent. The discrepant results may be explained, in part, by differences in skeletal site examined, baseline body weight, rate or magnitude of weight loss, calcium or protein intake, physical activity and duration of post-weight loss follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, even moderate weight reduction (B10%) in overweight or obese individuals both decreases bone mineral density (BMD) (Avenell et al, 1994;Pritchard et al, 1996;Ricci et al, 1998Ricci et al, , 2001Van Loan et al, 1998;Fogelholm et al, 2001;Jensen et al, 2001;Riedt et al, 2005;Villareal et al, , 2008 and accelerates bone turnover, as assessed by serum biomarkers of bone formation and resorption (Ricci et al, 1998Salamone et al, 1999;Holecki et al, 2007). Although these relatively short-term weight loss intervention studies, which are typically 3-6-month long, have demonstrated significant reductions in total body or regional BMD, long-term consequences of weight loss on bone mass, bone turnover and subsequent fracture remain relatively unknown.…”
Section: Introductionmentioning
confidence: 99%